193k views
4 votes
Consider the following pair of equations:

y = x + 4
y = −2x − 2

Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form.

User Vrakfall
by
5.5k points

1 Answer

6 votes

Answer:

(-2,2)

Explanation:

To solve the system, set the equations equal and solve for x.

x + 4 = -2x - 2

3x + 4 = -2

3x = -6

x = -2

Substitute x = -2 into one of the equations.

y = -2 + 4

y = 2

The solution is (-2,2).

User Can Aksoy
by
6.0k points